Faktor pendorong pemanfaatan layanan Voluntary Counselling and Testing (VCT) oleh lelaki suka dengan lelaki (LSL) di LSM gaya nusantara - Niken Ariska Prawesti; Purwaningsih Purwaningsih; Ni Ketut Alit Armini (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2018)
Abtract: Voluntary Counseling and Testing (VCT) is one of the government programs to prevent trans- mission of HIV/AIDS must done by Men Sex With Men (MSM). But there are still MSM who have not utilized VCT services. This study was aimed to analyze of the factors correlating with utilization VCT in MSM based on Health Belief Model at Surabaya region. Design used analytic with cross-sectional ap- proach. The 43 samples were chosen by purposive sampling. The independent variabels were perceived susceptibility, perceived seriousness, perceived benefits, perceived barriers, and cues to action. The de- pendent variabel was utilization VCT. Data were collected by using questonnaire and alayzed by chi square test. Results showed that perceived seriousness had correlation with VCT utilization (p=0,035), perceived seriousness had correlation with VCT utilization (p=0,039), perceived benefits had correlation with VCT utilization (p=0,019), perceived barrier had correlation with VCT utilization (p=0,008) and cues to action (p=0,037) had correlation with VCT utilization. Some factors in health belief model have a correlation with VCT utilization by MSM. It is recommended to officer GAYa Nusantara Civil Society Organizations to give adequate information frequently to the high risk people of HIV/AIDS. Keyword: VCT, utilization, MSM, health belief model Abstrak: Voluntary Counseling and Testing (VCT) adalah suatu program pemerintah untuk mencegah penularan HIV/AIDS yang perlu dilakukan olehLelaki Suka dengan Lelaki (LSL). Namun, masih terdapat LSL yang belum memanfaatkan layanan VCT. Penelitian ini bertujuan menganalisis faktor yang berhubungan dengan pemanfaatan VCT oleh LSL berdasarkan Teori Health Belief Model (HBM) di wilayah Surabaya. Desain penelitian analitik dengan pendekatan cross-sectional. 43 sampel dipilih dengan purposive sam- pling. Variabel independen adalah persepsi kerentanan, persepsi keseriusan,persepsi manfaat, persepsi hambatan, dan petunjuk bertindak. Variabel dependen adalah pemanfaatan VCT. Data dikumpulkan dengan menggunakan kuesioner dan dianalisisdengan uji chi square. Hasil menunjukkan bahwa kerentanan yang dirasakan memiliki korelasi dengan pemanfaatan VCT (p = 0,035), keseriusan yang dirasakan memiliki korelasi dengan pemanfaatan VCT (p = 0,039), manfaat yang dirasakan memiliki korelasi dengan pemanfaatan VCT (p = 0,019), hambatan yang dirasakan memiliki korelasi dengan VCT pemanfaatan (p = 0,008) dan isyarat untuk bertindak (p = 0,037) memiliki korelasi dengan pemanfaatan VCT. Persepsi kerentanan, persepsi keseriusan, persepsi manfaat, persepsi hambatan, dan petunjuk bertindak memiliki korelasi dengan pemanfaatan VCT oleh LSL.Disarankan kepada LSM GAYa Nusantara untuk sering memberikan informasi kepada orang-orang berisiko tinggi HIV / AIDS. Kata kunci: VCT, LSL, HIV, HBM